Paralympics and Its Athletes Through the Lens of the New York Times - Jeremy Tynedal; Gregor Wolbring (Sports, 2013)
The purpose of this article is to analyze the coverage of the Paralympics in the New York Times (NYT) from the first appearance of the term Paralympics in 1955 up to 2012. We analyzed a) the textual imagery (not imagery intrinsic to pictures) of the Paralympics and its athletes, b) the representation of views and hopes of Paralympians and c) the visibility of the Paralympics and Paralympians within the NYT. We found that NYT coverage of the Paralympics and Paralympians is minimal and often portrays Paralympic athletes in stereotypical ways, such as being supercrips or suffering entities. In regards to the portrayal of therapeutic assistive devices of Paralympic athletes in the NYT, four themes are evident: a) the advancement of technology, b) the hierarchy between different therapeutic assistive devices, c) the relationship between the device and the athlete and d) the affordability of the device. We submit that the portrayal of the Paralympics, as evident in the NYT, for the most part does not help to further the discussion around a) the future of the Paralympics and its role within society, b) the relationship between the Paralympics and the Olympics and c) barriers of sport participation faced by athletes with disabilities on all levels, from recreational to competitive sport.